2023
DOI: 10.3390/ijms24021077
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Saponins Play an Anti-Inflammatory Role by Targeting Caspase-11 Non-Canonical Inflammasome in Macrophages

Abstract: We previously reported that Korean red ginseng (KRG) exerts an anti-inflammatory role through inhibiting caspase-11 non-canonical inflammasome in macrophages; however, the components responsible for the anti-inflammatory role remained unclear. This study explored the anti-inflammatory activity of the KRG saponin fraction (KRGSF) in caspase-11 non-canonical inflammasome-activated macrophages. KRGSF inhibited pyroptosis, pro-inflammatory cytokine secretion, and inflammatory mediator production in caspase-11 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Third, although over 6000 naturally occurring flavonoids have been identified [ 84 ], only a few have been demonstrated to attenuate non-canonical inflammasome-associated inflammatory responses and diseases. Since substantial evidence has emphasized that non-canonical inflammasomes are key players in inducing inflammation, leading to the exacerbation of multiple inflammatory and infectious diseases [ 13 , 14 , 15 , 24 , 37 , 197 , 198 , 199 , 200 ], further studies to identify new flavonoids targeting non-canonical inflammasomes and to demonstrate their pharmacological roles in diseases associated with non-canonical inflammasomes need to be undertaken. Fourth, most of the studies demonstrated the preventive effect of flavonoids in the inflammatory responses and diseases, and the therapeutic effect of flavonoids should also be examined in the inflammatory responses and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although over 6000 naturally occurring flavonoids have been identified [ 84 ], only a few have been demonstrated to attenuate non-canonical inflammasome-associated inflammatory responses and diseases. Since substantial evidence has emphasized that non-canonical inflammasomes are key players in inducing inflammation, leading to the exacerbation of multiple inflammatory and infectious diseases [ 13 , 14 , 15 , 24 , 37 , 197 , 198 , 199 , 200 ], further studies to identify new flavonoids targeting non-canonical inflammasomes and to demonstrate their pharmacological roles in diseases associated with non-canonical inflammasomes need to be undertaken. Fourth, most of the studies demonstrated the preventive effect of flavonoids in the inflammatory responses and diseases, and the therapeutic effect of flavonoids should also be examined in the inflammatory responses and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of saponins extends to the inhibition of downstream effector functions, where interference with the proteolytic cleavage and activation of key inflammasome components, including caspase‐1, GSDMD (Gasdermin D), and pro‐inflammatory cytokines such as IL‐1β and IL‐18, is observed. Although the specific mechanisms underlying saponin modulation of inflammasome signaling pathways remain unspecified in the provided text, potential avenues include transcriptional inhibition, interference with proteolytic cleavage, and competitive inhibition of ligand–PRR interactions (Cho et al, 2023). The diverse effects exhibited by different saponins, sourced from Panax ginseng, Panax notoginseng, Panax japonicus , and Panax quinquefolius , further underscore their distinct impact on inflammasome activation.…”
Section: Anti‐inflammatory Properties Of Saponinsmentioning
confidence: 99%
“…Among them, ginsenosides, which are steroidal saponins, have been identified as major compounds that modulate numerous biological and physiological conditions in the body. Ginsenosides also have been reported to have pharmacological roles in multiple diseases by regulating various pathological conditions, such as inflammation, oxidative stress, lipogenesis, fibrosis, hypoxia, infection, and cellular apoptosis [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Recently, an increasing number of studies have demonstrated that ginsengs and ginsenosides play a pharmacological role in the pathogenesis and progression of NAFLD and NASH.…”
Section: Introductionmentioning
confidence: 99%